Characterization of diketopiperazine heterodimers as potential chemical markers for discrimination of two dominant black aspergilli, Aspergillus niger and Aspergillus tubingensis. (August 2020) - Xu, Ce; Xu, Kuo; Yuan, Xiao-Long; Ren, Guang-Wei; Wang, Xiao-Qiang; Li, Wei; Deng, Ning; Wang, Xiu-Fang; Zhang, Peng
Abstract: Black aspergilli are distributed worldwide and represent one of the most prolific sources of metabolites with biomedical and agrochemical interests. However, due to their similar morphological characteristics and insufficient molecular identification, the taxonomic classification of black aspergilli remains ill-defined. The production of specialised metabolites is often unique for species among black aspergilli and could be used as diagnostic chemical markers for species identification. In this study, chemical investigation of Aspergillus tubingensis OUCMBIII 143291 led to the discovery of the diagnostic chemical marker asperazine, a complex diketopiperazine heterodimer, as well as two previously undescribed analogues, asperazine B and C. In addition, an undescribed 2-benzylpyridin-4(1 H )-one-containing amide, pestalamide D, along with four known related metabolites were isolated. Their chemical structures, including their absolute configurations, were established on the basis of comprehensive spectral analysis and chiral HPLC analysis of the acidic hydrolysates. Asperazines B and C can serve as potential chemical markers for distinguishing A. tubingensis from A. niger, two representative species of black aspergilli that are usually incorrectly identified. Moreover, the isolated compounds were evaluated for their antifungal activity against eight phytopathogenic fungi including Alternaria alternata, A. brassicae, Botrytis cinerea, Colletotrichum lagenarium, Fusarium oxysporum, Gaeumannomyces graminis, Penicillium digitatum, and Valsa mali . Pestalamide D exhibited significant activities against B. cinerea, C. lagenarium, and V. mali, with MIC values of 4, 8, and 8 μg/mL, respectively, compared with the positive controls carbendazim (MICs = 8, 4, and 4 μg/mL) and prochloraz (MICs = 8, 8, and 4 μg/mL). The results of this study reveal two additional chemical markers and provide a powerful tool for the rapid identification of black aspergilli. Graphical abstract: Two previously undescribed diketopiperazine heterodimers were isolated as potential chemical markers from Aspergillus tubingensis OUCMBIII 143291. The undescribed 2-benzylpyridin-4(1 H )-one-containing amide was also characterized and exhibited significant antifungal activity. Image 1 Highlights: Three previously undescribed compounds were isolated from Aspergillus tubingensis OUCMBIII 143291. Asperazines B and C can serve as new chemical markers for distinguishing A. tubingensis from A. niger. The isolated compounds were evaluated for their antifungal activity. Pestalamide D exhibited significant activity against some phytopathogenic fungi.